Ibrutinib plus Bendamustine and Rituximab in Untreated Mantle-Cell Lymphoma - Wang, Michael L; Jurczak, Wojciech; Jerkeman, Mats; Trotman, Judith; Zinzani, Pier Luigi; Belada, David; Boccomini, Carola; Flinn, Ian W; Giri, Pratyush; Goy, Andre; Hamlin, Paul A; Hermine, Olivier; et al. (The New England journal of medicine, 2022)
BACKGROUND: Ibrutinib, a Bruton's tyrosine kinase inhibitor, may have clinical benefit when administered in combination with bendamustine and rituximab and followed by rituximab maintenance therapy in older patients with untreated mantle-cell lymphoma. METHODS: We randomly assigned patients 65 years of age or older to receive ibrutinib (560 mg, administered orally once daily until disease progression or unacceptable toxic effects) or placebo, plus six cycles of bendamustine (90 mg per square meter of body-surface area) and rituximab (375 mg per square meter). Patients with an objective response (complete or partial response) received rituximab maintenance therapy, administered every 8 weeks for up to 12 additional doses. The primary end point was progression-free survival as assessed by the investigators. Overall survival and safety were also assessed. RESULTS: Among 523 patients, 261 were randomly assigned to receive ibrutinib and 262 to receive placebo. At a median follow-up of 84.7 months, the median progression-free survival was 80.6 months in the ibrutinib group and 52.9 months in the placebo group (hazard ratio for disease progression or death, 0.75; 95% confidence interval, 0.59 to 0.96; P = 0.01). The percentage of patients with a complete response was 65.5% in the ibrutinib group and 57.6% in the placebo group (P = 0.06). Overall survival was similar in the two groups. The incidence of grade 3 or 4 adverse events during treatment was 81.5% in the ibrutinib group and 77.3% in the placebo group. CONCLUSIONS: Ibrutinib treatment in combination with standard chemoimmunotherapy significantly prolonged progression-free survival. The safety profile of the combined therapy was consistent with the known profiles of the individual drugs. (Funded by Janssen Research and Development and Pharmacyclics; SHINE ClinicalTrials.gov number, NCT01776840.).
Keywords: protokoly protinádorové kombinované chemoterapie; rituximab; lymfom z plášťových buněk; bendamustin hydrochlorid; progrese nemoci; inhibitory proteinkinas; pyrazoly; Humans; Protein Kinase Inhibitors; analýza přežití; piperidiny; Antineoplastic Combined Chemotherapy Protocols; Maintenance Chemotherapy; Pyrimidines; udržovací chemoterapie; Pyrazoles; lidé; Rituximab; indukce remise; Adenine; senioři; Piperidines; Remission Induction; adenin; Disease Progression; Aged; pyrimidiny; Survival Analysis; Bendamustine Hydrochloride; Lymphoma, Mantle-Cell